PENGARUH PENAMBAHAN LEVEL VITAMIN E-SELENIUM DALAM PAKAN TERHADAP FERTILITAS DAN DAYA TETAS TELUR HASIL PERSILANGAN AYAM SENTUL DENGAN AYAM RAS PETELUR - Nining Haryuni; Anna Lidyawati; Binti Khopsoh (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2019)
The purpose of this research was to obtain a dose of vitamin E-selenium addition in feed on the quality of hatched eggs resulting from crossing Sentul chicken with laying hens. This research used 200 hatching eggs produced from the 34-week-old Isa Brown strain of laying hens which were treated and inseminated using Sentul chicken males. The experimental method used in this research was a completely randomized design CRD) with 5 treatments and 5 replications with each replication consisting of 8 hatching eggs. The treatments feed in this research were as follows: P0 = Basal Feed, P1 = Basal Feed + 21.75 ppm vitamin E and 0.23 ppm selenium, P2 = Basal Feed + 43.5 ppm vitamin E and 0.46 ppm selenium, P3 = Basal Feed + 65.25 ppm vitamin E and 0.69 ppm selenium, P4 = Basal Feed + 87 ppm vitamin E and 0.92 ppm selenium. The results of this research were that the addition of vitamin E-selenium levels in feed had no significant effect (P> 0.05) on the weight of hatching eggs, fertility, embryo mortality and hatchability. Keywords: Vitamin E-Selenium Level, Feed, Hatching Eggs, Sentul Chicken ,Laying Hens